Analisis Pohon Cingkam (Bischofia javanica Blume) sebagai Aset Biodiversitas dalam Pembelajaran Ekologi Di SMAN 1 Tanoh Alas Aceh Tenggara - Wangi, Sari Sekar; Ulfa, Syarifah Widya (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The cingkam tree (Bischofia javanica Blume) is a type of tree that can be found in various areas of Sumatra and Java. Cingkam trees have the potential to be developed regarding biodiversity assets and the ecosystem that surrounds them. The existence of this tree is threatened due to human activities such as habitat loss, overexploitation, pollution and climate change. Therefore, conservation efforts and sustainable use of Cingkam trees are needed. This research aims to determine data on the concept of the cingkam tree as a biodiversity asset in ecological learning. This study is a descriptive qualitative research. Data collection was carried out through observation, interviews and documentation. The data obtained was then analyzed using coding themes, identifying themes and drawing conclusions. The results showed that (1) cingkam trees (Bischofia javanica Blume) have unique characteristics and ecological roles, and can improve students' understanding of ecological concepts such as adaptation, symbiosis, and ecosystem services; (2) the integration of cingkam tree characteristics in learning was proven to foster greater awareness and appreciation of biodiversity conservation among students; (3) cingkam trees can make a significant contribution to ecological education to encourage students to actively participate in local biodiversity conservation efforts.